Towards Accurate Biocompatibility: Rethinking Cytotoxicity Evaluation for Biodegradable Magnesium Alloys in Biomedical Applications - Angela De Luca; Roberta Ruggiero; Aurora Cordaro; Benedetta Marrelli; Lavinia Raimondi; Viviana Costa; Daniele Bellavia; Elisabetta Aiello; Matteo Pavarini; Antonio Piccininni; Marco Tatullo; Elisa Boanini; et al. (Journal of Functional Biomaterials)
Magnesium and its alloys represent promising candidates for biomedical implants due to their biodegradability and mechanical properties, which are similar to natural bone. However, their rapid degradation process characterized by dynamic pH fluctuations and significant hydrogen gas evolution during biocorrosion adversely affects both in vitro and in vivo assessments. While the ISO 10993-5 and 12 standards provide guidelines for evaluating the in vitro biocompatibility of biodegradable materials, they also introduce testing variability conditions that yield inconsistent results. To address these inherent characteristics of Mg alloys, developing improved methods that accurately simulate the physiological environment for in vitro biocompatibility testing is essential. This study introduces two novel extraction approaches for evaluating Mg alloys: a buffered solution utilizing PBS/DMEM with quaternary dilutions and a modified ISO standard protocol employing decuple dilution of conventional unbuffered extracts. The present findings establish that controlled optimization of extraction conditions, specifically buffer composition and dilution parameters, enables reliable in vitro cytotoxicity assessment of Mg alloys, providing a robust methodology that advances the preclinical evaluation of these promising biodegradable materials.